Mentoring at Maahad Tahfiz Al-Quran Negeri (Mtqn) In Pahang, Malaysia - et. al., Mohd Jamalil Ismail, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The implementation of tahfiz learning methods still has shortcomings and weaknesses as well as areas that need to be improved and given attention. In addition, the difficulty for a person to memorize the Qur'an also requires an effective and systematic memorization method to help them memorize and keep it from forgetting. The practice of mentoring method has had a positive effect when carried out at the state tahfiz maahad. This is because it can help the lecturer to deepen the weaknesses of each student who is guided in turn can help the students to reduce the stress they face. Lecturers also need to be more creative and proactive in implementing this mentee mentor program together with their respective mentees. Learning sessions will also be more enjoyable as a result of the close relationship between the lecturer and the students. This study was conducted to review previous studies related to the implementation of mentoring in maahad tahfiz Quran states in Malaysia